De novo Assembly of Transcriptomes From a B73 Maize Line Introgressed With a QTL for Resistance to Gray Leaf Spot Disease Reveals a Candidate Allele of a Lectin Receptor-Like Kinase - Welgemoed, Tanya; Pierneef, Rian; Sterck, Lieven; Van de Peer, Yves; Swart, Velushka; Scheepers, Kevin Daniel; Berger, Dave K. (Frontiers in Plant Science, 2020)
Gray leaf spot (GLS) disease of maize, caused by the fungus Cercospora zeina, is a threat to maize production globally. Understanding the molecular basis for quantitative resistance to GLS is therefore important for food security. We developed a de novo assembly pipeline to identify candidate maize resistance genes. Near isogenic maize lines with and without a QTL for GLS resistance on chromosome 10 from inbred CML444 were produced in the inbred B73 background. The B73-QTL line showed a 20% reduction in GLS disease symptoms compared to B73 in the field (p=0.01). B73-QTL leaf samples from this field experiment conducted under GLS disease pressure were RNA sequenced. The reads that did not map to the B73 or C. zeina genomes were expected to contain novel defence genes and were de novo assembled. A total of 141 protein coding sequences with B73-like or plant annotations were identified from the B73-QTL plants exposed to C. zeina. To determine if candidate gene expression was induced by C. zeina, the RNAseq reads from C. zeina challenged and control leaves were mapped to a master assembly of all the B73-QTL reads, and differential gene expression analysis was conducted. Combining results from both bioinformatics approaches led to identification of a likely candidate gene, which was a novel allele of a lectin receptor-like kinase named L-RLK-CML that (i) was induced by C. zeina; (ii) was positioned in the QTL region; and (iii) had functional domains for pathogen perception and defence signal transduction. The 817AA L-RLK-CML protein had 53 amino acid differences from its 818AA counterpart in B73. A second “B73-like” allele of the L-RLK was expressed at a low level in B73-QTL. Gene copy specific RT-qPCR confirmed that the l-rlk-cml transcript was the major product induced four-fold by C. zeina. Several other expressed defence-related candidates were identified including a wall associated kinase, two glutathione s-transferases, a chitinase, a glucan beta-glucosidase, a plasmodesmata callose-binding protein, several other receptor-like kinases, and components of calcium signalling, vesicular trafficking, and ethylene biosynthesis. This work presents a bioinformatics protocol for gene discovery from de novo assembled transcriptomes, and identifies candidate quantitative resistance genes.